Mother-Child Communication Interaction in Children with Cerebral Palsy - Preeja Balan; Manjula R (Journal of All India Institute of Speech and Hearing, 2007)
Verbal and nonverbal communication fulfills various communicative functions. Intention to communicate is an important communicative function, which further includes functions such as; (i) request for information; (ii) request for attention; (iii) request for object; (iv) information; (v) instruction (action); (vi) instruction (speech); (vii) confirmation (viii) denial. Typically developing children use intentional communication to have a preplanned effect on the mother; who is the most available communication partner for communication. It is clinically observed that in children with cerebral palsy (CP), the intentional communication between the child and the mother is often impaired. However, very few studies have addressed this issue in greater detail. The aim of this study is to describe the factors in intentional communication between the mother and nonspeaking child with cerebral palsy. Amongst the factors analyzed, instruction (action) and information were the most predominant functions observed in mother and child respectively. The other functions showed a hierarchical trend which is discussed in detail. The results revealed a communication asymmetry in the use of various communicative functions between mothers and their non speaking children with CP. Mothers were dominant communication partners while children were passive communicative partner as revealed from the frequency of occurrence of various communicative function.